2018
DOI: 10.3766/jaaa.16128
|View full text |Cite
|
Sign up to set email alerts
|

An Argument for Self-Report as a Reference Standard in Audiology

Abstract: Self-report is a reasonable reference standard for studies on the diagnostic accuracy of speech-recognition-in-noise tests. For individuals with normal pure-tone thresholds, the HINT demonstrated a higher degree of diagnostic accuracy than pure-tone thresholds for the detection of speech-recognition-in-noise disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 78 publications
5
26
0
Order By: Relevance
“…Using self-reported hearing loss as a single hearing screen question or a questionnaire on hearing functioning have both been proposed as valid screening methods. 3 , 11 , 12 , 14 - 18 The Hearing Handicap Inventory for the Elderly–Shortened (HHIE-S), for example, is a screening questionnaire consisting of ten questions evaluating the perceived social situational and emotional effects of hearing loss in the elderly. 16 Although the HHIE-S was standardized for individuals older than 65 years, Nondahl et al 16 found that it demonstrated lower sensitivity and accuracy in older individuals (65-92 years) compared with younger individuals (48-64 years).…”
Section: Introductionmentioning
confidence: 99%
“…Using self-reported hearing loss as a single hearing screen question or a questionnaire on hearing functioning have both been proposed as valid screening methods. 3 , 11 , 12 , 14 - 18 The Hearing Handicap Inventory for the Elderly–Shortened (HHIE-S), for example, is a screening questionnaire consisting of ten questions evaluating the perceived social situational and emotional effects of hearing loss in the elderly. 16 Although the HHIE-S was standardized for individuals older than 65 years, Nondahl et al 16 found that it demonstrated lower sensitivity and accuracy in older individuals (65-92 years) compared with younger individuals (48-64 years).…”
Section: Introductionmentioning
confidence: 99%
“…The authors stated that tests designed to evaluate auditory function in quiet would not provide an accurate measure of the ability to hear speech in everyday noisy environments. This has been demonstrated in multiple studies where individuals with normal pure-tone thresholds have reported speech perception difficulties in the presence of noise (King, 1954;Saunders and Haggard, 1989;Vermiglio, Soli, et al, 2017).…”
Section: Introductionmentioning
confidence: 75%
“…A review of the literature has shown that SRN evaluations reveal information about listening ability in daily listening environments unavailable from puretone thresholds (King, 1954;Saunders and Haggard, 1989;Vermiglio, Soli, et al, 2017). Unfortunately, SRN evaluations are not commonly used in the clinic (ASHA, 2015;Mueller, 2016).…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations